Atypical dermatomyositis with positive anti-nuclear matrix protein 2 antibodies complicated by rhabdomyolysis syndrome: a case report and literature review - Zhang, Zhengyi; Jiang, Dawei; Wei, Tao; Long, Kunlan (Frontiers in Immunology, 2026)
BackgroundIdiopathic inflammatory myopathies (IIMs) are a group of systemic disorders characterized by chronic autoimmune dysregulation; their hallmark is symmetric proximal muscle weakness, often with characteristic cutaneous eruptions in dermatomyositis subtypes. Anti–nuclear matrix protein-2 (NXP-2) antibodies are classified as myositis-specific autoantibodies, yet their prevalence remains persistently low. Adult dermatomyositis associated with NXP-2 positivity exhibits a distinctive phenotype in terms of clinical manifestations, complications, and prognosis—particularly an elevated malignancy risk—and is now regarded as an independent subset within the IIMs spectrum. However, reported frequencies vary widely across cohorts, and cases complicated by rhabdomyolysis are exceedingly rare, posing major challenges to timely recognition and optimal management.Case presentationWe report a 56-year-old man who developed rhabdomyolysis syndrome after a clear precipitating event. Despite aggressive fluid resuscitation, urinary alkalinization with sodium bicarbonate, and continuous renal-replacement therapy to clear myoglobin, systemic manifestations continued to progress. A comprehensive re-evaluation led to the diagnosis of adult anti-NXP-2 antibody-positive dermatomyositis complicated by rhabdomyolysis. High-dose pulsed glucocorticoid therapy combined with supportive measures achieved disease control and gradual stabilization, allowing transfer to a specialized unit in a stable condition. During subsequent follow-up, the patient remained on low-dose glucocorticoids without any significant adverse effects.ConclusionAdult anti-NXP-2 antibody-positive dermatomyositis complicated by rhabdomyolysis has been documented only sporadically; its co-occurrence is estimated at <1%, placing it in the ultra-rare category. The precise pathogenic role of this antibody in systemic autoimmunity remains undefined, and systematic evidence linking it to rhabdomyolysis is lacking. Future multi-omic profiling and functional studies are required to determine whether the two disorders share a common mechanistic pathway.